COMPETITION BETWEEN MAJOR POWERS IN THE MIDDLE EAST: THE US, RUSSIA, CHINA (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes geopolitical dynamics in the Middle East in the context of competition and interaction between the US, China, and Russia, and examines the consequences of these processes for the states of Central Asia. The paper examines the key policy areas of these powers, including their energy, military, and diplomatic activities, as well as their participation in regional organizations such as the SCO and BRICS. Particular attention is paid to the events of 2024–2025, including the expansion of US military agreements with Middle Eastern allies, China's intensified activity within the Belt and Road Initiative, and Russia's strengthening of its position through strategic partnerships with Iran and Arab monarchies. Based on a comparative analysis, the study identifies the distinctive features of each side's approach and assesses their impact on the security, economic development, and political stability of Central Asia. The results of the study show that the region is turning into an arena of complex trilateral rivalry, where Central Asian states are forced to seek a balance between global power centers.